ANALYSIS OF DELAY ENTRY AND PLANNING OF PARKING GATES QMALL BANJARBARU - Ali Charoenplien; Puguh Budi Prakoso (Universitas Lambung Mangkurat, 2021)
Qmall Banjarbaru is located at Jalan Ahmad Yani KM. 37. The existence of Qmall Banjarbaru caused the impact of increased traffic density and decreased speed in the surrounding road network. With the increasing movements that occur from Qmall Banjarbaru, it will potentially be the cause of congestion between vehicles that will enter the Qmall Banjarbaru with vehicles moving straight on Jalan Ahmad Yani KM. 37. The purpose of this research is to know the influence of delay entrance parking Qmall Banjarbaru against the performance of Jalan Ahmad Yani KM. 37.This research conducted a field survey that aims to find volume data on the road, the time of parking door service, the number of vehicles that enter the parking, the time delay the parking door, and the length of the delay that occurs on the parking door. From the results of data analysis using the Calculation of field survey (realistic) data obtained the distance of the parking door previously 16.5 meters to be redated to 25 meters and the parking door that originally had two doors of parking service made into three doors parking service. This change was made to delay enter parking Qmall Banjarbaru does not reach Jalan Ahmad Yani Km. 37.